دور الثقافة الإسلامية في كيفية تطبيق إدارة الجودة الشاملة داخل وزارة النفظ الليبية - Aiman IMuhammad Muhammad Al-Busifi
The aim of this study is to measure the role of Islamic culture in the application of total quality management within the Oil Libyan Ministry of Oil, in order to know the advantages of Islamic culture in relation to TQM, and to identify the problems and challenges facing of implementing it. On the other hand, the study aimed to identify the personal and functional differences in both Islamic culture and the possibility of implementing Total Quality Management, which is attributed to personal and functional characteristics within the ministry (job, experience, educational level, training).The researcher used a descriptive analytical method in conducting this study as the most appropriate research method. The questionnaire was used as a main tool for collecting data. He had also used the simple and multiple regression tests that were applied to statistically understand the relationship of the sample. The size of the sample (200 individuals) of the employees in the Oil Libyan Ministry of which was selected from an purposive sample approach and to conclude the most important results in this study and the presence of an inverse relationship between the role of Islamic culture and the problems associated in applying total quality management such as (administrative problems, technical problems and human resource problems) and in what sense it would approachable to take this direction to apply Islamic management and how it would reduce the occurrence of problems associated in applying total quality, the study showed that there are no differences in Islamic culture due to the personal and functional variables.